Effect of Azotobacter sp. and Cow Manure on Nitrogen Availability in Saline Soil, Root Length, and Vitamin C Content of Tomato - Aulifia Nisak Aisyah; Rossyda Priyadarshini; Siswanto Siswanto (The University of Lampung, 2025)
Nitrogen is a macronutrient for plants, but its availability in saline soil is a limiting factor, making it difficult to cultivate plants. This study aims to examine the effect of the combination of Azotobacter sp. and cow manure in increasing the available N of saline soil, and to obtain the best combination in increasing the growth of tomato plants in saline soil. This research was conducted in the greenhouse and laboratory of UPN